A Positive Psychological Approach to Suicide Theory, Research, and Prevention (Advances in Mental Health and Addiction,, 2018)
This inspiring resource presents theories, findings, and interventions from Positive Suicidology, an emerging strengths-based approach to suicide prevention. Its synthesis of positive psychology and suicidology theories offers a science-based framework for promoting wellbeing to complement or, if appropriate, replace traditional deficit-driven theories and therapies used in reducing suicidal thoughts and behaviors. Coverage reviews interpersonal, intrapersonal, and societal risk factors for suicide, and identifies protective factors, such as hope and resilience, that can be enhanced in therapy. From there, chapters detail a palette of approaches and applications of Positive Suicidology, from the powerful motivating forces described in Self-Determination Theory to meaning-building physical and social activities. Among the topics covered: Future-oriented constructs and their role in suicidal ideation and enactment. Gratitude as a protective factor for suicidal ideation and behavior: theory and evidence. Considering race and ethnicity in the use of positive psychological approaches to suicide. The Six R's framework as mindfulness for suicide prevention. Community-based participatory research and empowerment for suicide prevention. Applied resiliency and suicide prevention: a strengths-based, risk-reduction framework. Psychotherapists, counselors, social workers, psychiatrists, and health psychologists, as well as educators, clergy and healthcare professionals, will find A Positive Psychological Approach to Suicide an invaluable source of contemporary evidence-based strategies for their prevention and intervention efforts with suicidal clients.